Himalayan wolf distribution and admixture based on multiple genetic markers. (19th February 2020) - Werhahn, Geraldine; Liu, Yanjiang; Meng, Yao; Cheng, Chen; Lu, Zhi; Atzeni, Luciano; Deng, Zhixiong; Kun, Shi; Shao, Xinning; Lu, Qi; Joshi, Jyoti; Man Sherchan, Adarsh; et al.
Abstract: Aim: We explore the phylogeography of Himalayan wolves using multiple genetic markers applied on a landscape‐scale dataset and relate our findings to the biogeographic history of the region. Location: Himalayas of Nepal, the Tibetan Plateau of China and mountain ranges of Central Asia. Taxon: Himalayan wolf (also called the Tibetan wolf), Canis lupus chanco . Methods: We present a large‐scale, non‐invasive study of Himalayan wolves from across their estimated range. We analysed 280 wolf scat samples from western China, Kyrgyzstan and Tajikistan at two mtDNA loci, 17 microsatellite loci, four non‐synonymous SNPs in three nuclear genes related to the hypoxia pathway, and ZF genes on both sex chromosomes. Results: Our results corroborate previous studies showing that the Himalayan wolf forms a distinct lineage adapted to high altitudes in excess of 4, 000 m elevation. We found a correlation between hypoxia adaptation and the divergent Himalayan wolf mtDNA haplotype found across the Tibetan Plateau of Qinghai, the Tibetan Autonomous Region and the Nepalese Himalayas. We identified a region of admixture between Himalayan and grey wolves at the boundary of their distributions, where the Tibetan Plateau elevation gradually drops. Main Conclusion: Based on multiple genetic markers, the Himalayan wolf forms a reciprocally monophyletic lineage with a unique adaptation to high altitude. We propose that the divergence of the lineage is related to past uplift of the region, and that the lineage maintains its high‐altitude niche, in part, by means of its genetic adaptation to hypoxia. We conclude that the Himalayan wolf merits taxonomic recognition and designation as an evolutionary significant unit (ESU).